DESAIN PENGEMBANGAN E-MODUL INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR PADA SISWA SMP NEGERI 1 HULU GURUNG - Syaiful, Syaiful; Astuti, Indri; Afandi, Afandi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research was intended to design interactive e-module development in improving student learning outcomes at SMP Negeri 1 Hulu Gurung. The research method in this study is R&D (Reaserch & Development) which refers to the ADDIE theory. Researchers concentrate on the Analyze to Design aspects of the ADDIE development model (Branch, 2009). The design designed in this study was an interactive e-module intended to improve student learning outcomes in excretion system material which was previously identified as not optimal based on the output of the learning analysis carried out by researchers at the needs analysis stage. The e-module design designed using Canva by utilizing template software that is integrated with other product content, interactive e-modules containing covers, instructions for using the e-module, preface, table of contents, core competencies, basic competencies, concept maps of the excretion system material people, materials, learning videos, evaluations, author profiles. In addition to material presentation, designers, in this case researchers, add videos to optimize student understanding which are published in the form of links which are then used as teaching materials both inside and outside the classroom at research locations and can be used by students in other schools as well as part of product dissemination or follow-up. development to be carried out thereafter.